Comparing the benefits of postoperative adjuvant chemotherapy vs. observation for stage IB non-small cell lung cancer: a meta-analysis - Li, Ranhua; Yang, Guixue; Tian, Ye; Tian, Dali (Journal of Thoracic Disease, 2019)
Background: The aim of this meta-analysis was to compare the benefits of postoperative adjuvant chemotherapy vs. observation for stage IB non-small cell lung cancer (NSCLC). Methods: A literature search was performed in PubMed, Embase, and Cochrane Library databases, and stage IB NSCLC patients were assigned to the postoperative adjuvant chemotherapy and observation groups. The 5-year overall survival (OS), 5-year disease-free survival (DFS), local recurrence, and distant metastasis were then assessed. In addition, statistical analysis was conducted using Review Manager 5.3 software. Results: The meta-analysis involved nine articles and included 1,645 stage IB patients. There was no significance in the 5-year OS [relative risk (RR) =1.05; 95% confidence interval (CI): 0.98–1.13; P=0.14] and 5-year DFS (RR =1.29; 95% CI: 0.97–1.72; P=0.08) between the postoperative adjuvant chemotherapy and observation groups. However, there was a significant difference in local recurrence (RR =0.43; 95% CI: 0.23–0.80; P=0.007) and distant metastasis (RR =0.68; 95% CI: 0.48–0.97; P=0.03) between the two groups. Conclusions: Adjuvant chemotherapy might not be recommended for stage IB NSCLC.